Seminar on Early Marriage Administration in Tegal Village, Kemang District, Bogor Regency - Avid Aji Setyawan; Dinda Yulianti; Siti Masitoh; Irfan Farhansyah (LPPM UIKA Bogor, 2023)
The Early Marriage Administration Seminar in Tegal Village is an event that aims to increase awareness of the village community about the importance of early marriage administration. Early marriage is a phenomenon that still often occurs in various regions, including in Tegal Village. This seminar aims to provide an understanding of marriage regulation, the rights and responsibilities of young couples, and the importance of education before marriage. In this seminar, participants will get information about legal marriage procedures by state law, as well as the positive impact of marriages performed at the right age. In addition, they will also be invited to participate in discussions and questions and answers, so that they can answer various questions they have. It is hoped that through this seminar, the people of Tegal Village will be more aware of the importance of proper marriage administration, to reduce illegal early marriage and provide better protection for young couples. This seminar is also expected to be the first step towards a positive change in the mindset and practice of marriage in this village.